Bisphenol A promotes macrophage proinflammatory subtype polarization via upregulation of IRF5 expression in vitro. (October 2019) - Lu, Xiaotong; Li, Meiling; Wu, Changhao; Zhou, Chengfan; Zhang, Jiaxiang; Zhu, Qixing; Shen, Tong
Abstract: Exposure to environmental endocrine-disrupting chemical Bisphenol-A (BPA) is closely associated with an imbalance of immune homeostasis, but the underlying mechanisms are not fully understood. In the present study, the effects of BPA on the polarization of mouse peritoneal macrophages were investigated in vitro. Environmentally relevant low concentrations of BPA treatment under M1 type polarization conditions increased the number of M1 subtype macrophages, the gene expression of M1 phenotypic marker CD11c and the activity and gene expression of M1 functional marker iNOS, as well as the production of pro-inflammatory cytokines. However, The same dose BPA treatment under M2 type polarization conditions reduced the number of M2 subtype macrophages, the gene expression of M2 phenotypic marker CD206 and the activity and gene expression of M2 functional marker Arg-1, along with the production of anti-inflammatory cytokines. We also identified that the expression of transcription factor IRF5 was upregulated by BPA exposure in M1 macrophages under M1 type polarization conditions. Our results demonstrate that BPA promotes macrophage polarization toward proinflammatory M1 subtype and M1 activity, associated with upregulated expression of IRF5, while BPA inhibits macrophage toward anti-inflammatory M2 subtype polarization. These findings provide new insight into the link between exposure to BPA and impairment of immune functions. Highlights: BPA promotes macrophage polarization toward proinflammatory M1 subtype in vitro. BPA inhibits macrophage toward anti-inflammatory M2 subtype polarization in vitro. BPA enhances pro-inflammatory cytokines secretion while reduces anti-inflammatory cytokines production. BPA promotes macrophage polarization toward proinflammatory M1 subtype associated with upregulated expression of IRF5.